2017
DOI: 10.1016/j.ultsonch.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound on microbial growth and enzyme activity

Abstract: Nowadays, ultrasound is widely used in many aspects. In the last few years, many papers have concentrated on the applications of ultrasound in engineering, chemistry, medicine, physics and biology, but few in biological effects such as the acceleration effects on proliferation of microbial cells, the inactivation effects on microorganisms and the influences on the activities of enzyme. Thus, the objective of this review is to investigate the biological effects of ultrasound on these aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
167
1
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(185 citation statements)
references
References 50 publications
7
167
1
10
Order By: Relevance
“…Polyphenol oxidase activity was reduced (up to 38%) for longer treatment time (30 min) at 200 W. Enzyme inactivation by ultrasonic treatment has been related to the process of cavitation, which is characterized by the creation, development, and implosion of small gas bubbles during treatment . The generation of high temperature, pressure, shear force, and formation of free radicals due to the sonolysis of water molecules during ultrasonic treatment leads to enzyme inactivation …”
Section: Resultsmentioning
confidence: 99%
“…Polyphenol oxidase activity was reduced (up to 38%) for longer treatment time (30 min) at 200 W. Enzyme inactivation by ultrasonic treatment has been related to the process of cavitation, which is characterized by the creation, development, and implosion of small gas bubbles during treatment . The generation of high temperature, pressure, shear force, and formation of free radicals due to the sonolysis of water molecules during ultrasonic treatment leads to enzyme inactivation …”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is essential to improve the enzyme activity. Ultrasound is a potential method for modifying enzyme activity (Delgado‐Povedano & Castro, ; Huang, Chen, et al., ; Nadar & Rathod, ), and many researchers have used it to improve food enzymes. For example, Dalagnol, Silveira, Silva, Manfroi, and Rodrigues () found that ultrasound improved the activities of pectinase, xylanase, and cellulase.…”
Section: Introductionmentioning
confidence: 99%
“…The low frequency ultrasound can improve the permeability of cells by forming transient pores on the cell membrane. These pores increase the transfer of substances across the membrane and the secretion of metabolites like intracellular enzymes and subsequently stimulate cellular growth and proliferation (Ewe, Wan‐Abdullah, Alias, & Liong, ; Huang et al, ; Mota et al, ; Yeo & Liong, ). Dai et al () investigated the effect of sonication on the growth of Saccharomyces cerevisiae and its membrane permeability.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, the absorbance was read at 560 nm (Wang et al, 2006). , & Liong, 2012;Huang et al, 2017;Mota et al, 2018;Yeo & Liong, 2013). Dai et al (2017) investigated the effect of sonication on the growth of Saccharomyces cerevisiae and its membrane permeability.…”
Section: Scavenging Activity Of Superoxide Anion Radicalmentioning
confidence: 99%